Performance evaluation of Aqua Crop model for conservation agriculture based direct seeded rice (Oryza sativa) - MOHAMMAD, ALI; SUDHISHRI, SUSAMA; SINGH, MAN; DAS, T K; SHARMA, V K; DWIVEDI, NEETA (The Indian Journal of Agricultural Sciences, 2018)
Direct seeded rice (DSR) with conservation agriculture (CA) can be a good option to replace the highly water consuming puddle transplanted rice (Oryza sativa L.) for producing more per unit area with less water. The predictionof rice productivity through crop growth model is significant for further planning in water savings. There are various crop growth models used for predicting rice yield, but less information available on prediction of direct seeded rice under conservation agriculture. Therefore, the water driven FAO AquaCrop model (v.5.0) which requires minimum datasets was applied to the data generated from two years (2014 and 2015) field experimentation carried out in Research Farm, ICAR-Indian Agricultural Research Institute, New Delhi. The experiment was laid out in randomized block design in continuing experiment (5-6th year) with six CA practices in DSR and two puddle transplanted rice treatments and rice variety was PRH 10. The model was calibrated and validated using the data sets of kharif seasons of 2014 and 2015, respectively. The validated model prediction error statistics, i.e. root mean square error (RMSE), model efficiency (ME), index of agreement (d) and coefficient of determination (R2) for grain yield, were 0.58, 0.72, 0.93, 0.96, and for biomass 1.11, 0.85, 0.95, 0.96, respectively, for all the treatments under CA based DSR treatments. It was observed under conservation agriculture with different levels of crop residues, the predicted yield have a good fit with the observed values with acceptable accuracy. Thus, water-driven FAO AquaCrop model can be applied to predict the yield of direct seeded rice grown under conservation agriculture in the semi-arid regions of India, particularly Indo-Gangetic plain (IGP).